2019
DOI: 10.4103/jlp.jlp_168_18
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble FMS-like tyrosine kinase-1 in ectopic pregnancy

Abstract: CONTEXT: The diagnosis of an ectopic pregnancy (EP) requires the usage of serial beta-human chorionic gonadotropin (hCG) measurements and ultrasonography to locate the gestational sac. With the rising trends in its incidence, a rapid, noninvasive biomarker to detect this condition at the earliest can aid in decreasing the morbidity and mortality linked with EP. AIMS: This study was performed to determine the serum level of soluble FMS-like tyrosine kinase-1 (sFLT-1) at 4–10-week gestation in EP and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The mechanism behind the reduction in the level of sFLt-1 in EP may be related to increased consumption due to the subsequent binding of the sFLt1 receptor to the excessively expressed VEGF, or a decrease in sFLt-1 production or both. This was in line with other studies finding that showed the level of sFLt-1 level was significantly lower in ectopic pregnancy and miscarriage compared to normal pregnancy, such as Daponte et al [9] study in which the mean value of sFLt-1 was significantly lower in EP (178.16 ±76.03 pg/ml) and miscarriage (399.42 ± 337.54 pg/ml) compared to women with viable IUP (1390.32 ± 655.37pg/ml) and in the Selvarajan et al [10] study that reported that the sFLt-1 level is significantly lower in the ectopic group (419 pg/ml) compared to IUP( 898 pg/ml). The differences in the mean sFLt-1 reported in our study with studies of Selvarjan et al and Daponate et al [9,10].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The mechanism behind the reduction in the level of sFLt-1 in EP may be related to increased consumption due to the subsequent binding of the sFLt1 receptor to the excessively expressed VEGF, or a decrease in sFLt-1 production or both. This was in line with other studies finding that showed the level of sFLt-1 level was significantly lower in ectopic pregnancy and miscarriage compared to normal pregnancy, such as Daponte et al [9] study in which the mean value of sFLt-1 was significantly lower in EP (178.16 ±76.03 pg/ml) and miscarriage (399.42 ± 337.54 pg/ml) compared to women with viable IUP (1390.32 ± 655.37pg/ml) and in the Selvarajan et al [10] study that reported that the sFLt-1 level is significantly lower in the ectopic group (419 pg/ml) compared to IUP( 898 pg/ml). The differences in the mean sFLt-1 reported in our study with studies of Selvarjan et al and Daponate et al [9,10].…”
Section: Discussionmentioning
confidence: 91%
“…Serum soluble FMS-like tyrosine kinase-1 has been studied extensively for diagnosis and prediction of many gynecological conditions like preeclampsia, preterm birth, growth restriction, stillbirth, and miscarriage [16,18,19]. However, studies on its role in ectopic pregnancy are still spared [10] In the current study, the mean βhCG was significantly higher among IUP group (24851.07 IU/L) in comparison to ectopic pregnancy (6270.87 IU/L) and miscarriage (9783.67 IU/L),…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A disaster in human reproduction is ectopic pregnancy in which fetus implants outside the uterine cavity and inevitably results in the death of the fetus. 1 Although ectopic pregnancy has been recognized for many years, it is a growing problem, affecting approximately 2% of all pregnancies. 2 There are also regional differences in its incidence, 18/1000 in India, 7.4/1000 births in Bangladesh, and 1:128 to 1:130 pregnancies in Pakistan.…”
Section: Introductionmentioning
confidence: 99%